Oncosis is the predominant type of cell death in rhabdomyolysis following exertional heat stroke - Chengcheng Li; Yang Liu; Handing Mao; Wenjun Yang; Shuyuan Liu; Yi Shan (PLoS ONE, 2025)
Background Rhabdomyolysis (RM), particularly heat exhaustion-associated rhabdomyolysis (ehsRM), is a significant clinical issue associated with high mortality and healthcare costs. However, the cellular death mechanisms remain incompletely understood. Oncosis, a form of passive cell death distinct from apoptosis, is characterized by cell swelling and triggered by ATP depletion. Additionally, porimin, a specific biomarker, can uniquely identify oncosis. This study aims to investigate the role and mechanisms of oncosis in both in vitro and in vivo models of ehsRM. Objective This study aims to investigate the role and mechanisms of oncosis in both in vitro and in vivo models of ehsRM. Methods In the in vitro study, 6-8-week-old male rats were subjected to treadmill exercise at an ambient temperature of (39.5 ± 0.5)°C and relative humidity of 50%-60%, at a speed of 15 meters per minute until their core body temperature (Tc) reached 43.0°C to establish a heatstroke animal model. Skeletal muscle and blood samples from the gastrocnemius were collected for cytokine, biochemical, and histopathological analyses. Pathological findings revealed decreased muscle fiber density, structural disarray, swelling, degeneration, and hemorrhage. Ultrastructural analysis showed cell swelling, structural disarray, cytoplasmic vacuolation, mitochondrial swelling and degeneration, loss of cristae, and nuclear degeneration, indicating myocyte swelling and necrosis. Porimin, CytC, Bax, and caspase-1 expression increased, while Bcl-2 expression decreased. JC-1 staining indicated a decline in mitochondrial membrane potential and dysfunction. ATP levels decreased, and reactive oxygen species (ROS) production increased. In the in vivo study, HSKMC cells were subjected to 4 hours of heat shock at 43°C to establish a heatstroke-induced rhabdomyolysis cell model. Electron microscopy revealed cell swelling, cytoplasmic vacuolation, mitochondrial swelling and degeneration, and nuclear swelling; late-stage (necrotic-like death) was characterized by nucleolar dissolution, nuclear fragmentation, chromatin condensation, and collapse of cytoplasmic structures. After 24 hours post-modeling, the proportion of double-positive cells (porimin + /PI+) and ROS levels significantly increased, as did porimin expression, while mitochondrial membrane potential and ATP levels significantly decreased. The proportion of Annexin V + /PI + double-positive cells and caspase-3 levels showed no significant changes. Results In both in vitro and in vivo studies, oncosis played a crucial role in ehsRM. Pathological and ultrastructural analyses demonstrated cell swelling, structural disarray, mitochondrial damage, and nuclear degeneration. Porimin, CytC, Bax, and caspase-1 expression increased, while Bcl-2 expression decreased. ATP levels decreased, and ROS production increased. In the in vivo study, the proportion of porimin + /PI + double-positive cells and ROS levels significantly increased, while mitochondrial membrane potential and ATP levels significantly decreased. The proportion of Annexin V + /PI + double-positive cells and caspase-3 levels showed no significant changes. Conclusion Oncosis is predominant in ehsRM, involving mitochondrial dysfunction, ATP depletion, and oxidative stress.